The role of teachers in assessing educational quality - LongAn Dangnguyen (Revista on line de Política e Gestão Educacional)
The purpose of this paper is to answer the question "Can teachers do the educational quality evaluation tasks?", in the context of lacking experts or well-trained staff to do this task in low and middle-income countries, such as Vietnam. In this study, the training on knowledge, soft skill, performance, and attitude were tested as the tool improving the teachers' performance in evaluating education quality. The study was based on a quasi-experimental design, cross-disciplinary, and mixed-evaluation methods. The study is cross-disciplinary as it examines the difference between the comparison and intervention group concerning personal factors and job attitude. The findings indicate that providing knowledge, soft skill practice, and positive job attitude help to improve the staff's performance in assessing the quality of education. The findings presented in this paper provide evidence of effectiveness of the education quality evaluation skills training in schools.